Effect of weekly physical activity frequency on weight loss in healthy overweight and obese women attending a weight loss program: a randomized controlled trial - Madjd, Ameneh; Taylor, Moira A.; Shafiei Neek, Leila; Delavari, Alireza; Malekzadeh, Reza; MacDonald, Ian A.; Farshchi, Hamid R. (American Society for Nutrition, 2016)
ABSTRACT Background: The effect of intensity and duration of physical activity (PA) on weight loss has been well described. However, the effect of the frequency of weekly PA on weight loss is still unknown. Objective: The purpose of this study was to evaluate the effect of the frequency of weekly PA sessions while maintaining the same total activity time on weight loss during a 24-wk weight loss program. Design: Overweight and obese women [n = 75; body mass index(BMI; in kg/m2): 27–37; age: 18–40 y] who had a normally sedentary lifestyle were randomly allocated to 1 of 2 intervention groups: a high-frequency physical activity (HF) or a low-frequency physical activity (LF) group. The HF group included 50 min/d PA, 6 d/wk (300 min/wk). The LF group included 100 min/d PA, 3 d/wk (300 min/wk). Both groups were advised to follow the same dietary weight loss program. Results: Both groups showed a significant decrease in anthropometric measurements and significant improvements in cardiometabolic disease risk characteristics over the 24 wk of the study. Compared with the HF group, the LF group had a greater decrease in weight (mean 6 SD; LF: 9.58 6 3.77 kg; HF: 7.78 6 2.68 kg; P = 0.028), BMI (LF: 3.62 6 1.56; HF: 2.97 6 1.02; P = 0.029) and waist circumference (LF: 9.36 6 4.02 cm; HF: 7.86 6 2.41 cm; P = 0.031). However, there were no significant differences in carbohydrate metabolism characteristics or lipid profile after the 24 wk of intervention. Conclusion: Weekly PA undertaken over fewer sessions of longer duration during the week could be more effective for weight loss than when undertaken as more frequent shorter sessions in overweight and obese women on a weight loss program. This may be helpful for those who are neither willing nor able to schedule time for PA almost every day to achieve weight loss. This trial was registered at www.irct.ir as IRCT201402157754N4.